Comprehensive power shifts in the making: the rise of China’s policy and knowledge transfer partnerships with the United Nations - Haug, S; Trajber Waisbich, L (Wiley, 2024)
China and the United Nations (UN) have set up a growing number of partnerships to transfer Chinese domestic development policies across the South. By examining these partnerships through a power shift lens, we suggest that UN-endorsed policy transfer processes can function as a window into shifting international cooperation dynamics. The paper first provides an overview of the evolution and key characteristics of China–UN policy transfer partnerships, focusing on China's trajectory as a provider of policy solutions. It then analyses the extent to which the evolving partnership landscape contributes to and reflects shifts in China's compulsory, institutional, structural and productive power. Overall, we argue that policy transfer partnerships contribute to comprehensive power shifts in the making: while empirical data point to China's often (still) limited and evolving ability to influence the actions of others, our findings provide evidence for increasing levels of Chinese influence in and through policy transfer partnerships across all power types.